Tax Expenditure Reporting and Its Use in Fiscal Management : A Guide for Developing Economies. (IMF How To Notes; How-To Note ;, 2019)
This note aims to inform governments on how to account for tax expenditures and use that information in fiscal management. The emphasis is on developing and emerging market economies, where the use of such accounts is in its infancy because of data constraints, insufficient human and financial resources, and weak fiscal institutions. Most developing economies, more-over, do not have tax policy units in their Ministry of Finance to provide analytical support to the government and legislature that integrates all revenue policy aspects. As a result, the tax policy framework can be fragmented: line ministries compete in the provision of sectoral tax incentives, but do not report on their cost. The note is organized as follows. The second section outlines the role that tax expenditure measurement and reporting can play in fiscal management. The third section provides a step-by-step approach on how tax expenditure accounts can be built, with emphasis on data, methods and models, and institutional requirements. The section is concerned primarily with the direct cost of tax expenditures-that is, the revenue forgone because of them. It does not deal with their indirect costs, which could include economic efficiency losses and additional tax administration resources, and it does not address assessment of the benefits of tax expenditures. The fourth summarizes the current status of tax expenditure reporting in developing economies, with some reference to advanced economies. The last section concludes.